Frequency and Correlation of Body Mass Index and Waist-Hip Ratio with Fasting Glycemia and Blood Pressure in High School Students from Mexico - Lourdes Adriana Medina-Gaona; Nallely Enríquez-Sánchez; Carla Elizabeth Mejía- Ramírez; Nathalia de Jesús Orueta-Mondragón; Heriberto Medina-Franco; Yareri Sandoval-Morales; Tanya Plett-Torres (University Library System, University of Pittsburgh, 2018)
Background: Overweight/obesity is a global public health problem in adolescents. Its frequency is increasing as similar to diabetes, hypertension, health expenses, and poor quality of life. Thus, detecting overweight/obesity early in life promises a positive impact on the world's health. Methods: In a cross-sectional study, differences were explored between glycemia and blood pressure according to BMI, WHR, age, sex, number of daily meals and family history of chronic diseases in high school students from Mexico City. Results: The prevalence of overweight and obesity in the participants (115) was 26% and 7%, respectively. Fasting glycemia (mg/dL) was higher in students aged ≤17 vs. ≥18 (91.45±7.96 vs 87.59±10.06, p=0.038). All hyperglycemic students and with android adipose distribution were women. Compared to the other participants, overweight students had higher systolic (107.24±12.31 vs 115.73±15.28, p=0.003) and diastolic (70.99±10.93 vs 76.27±13.02, p=0.033) mean values (mmHg). Systolic values were higher in obesity (108.77±13.03 vs 118.63±18.38, p=0.048). Men had a higher frequency of systolic (32%, p=0.001) and diastolic (37%, p=0.023) prehypertension/hypertension than women (8% and 17%, respectively). Systolic prehypertension/hypertension was common in overweight (47% vs 53%, p=0.008). Skipping meals was common in students with family history of hypertension (13% vs 87%, p=0.005). Conclusion: The prevalence of overweight was higher and of obesity was lower than the one reported in ENSANUT 2016 (22.4% and 13.9%, respectively). Sex differences in blood glucose and pressure were obtained: men had higher blood pressures and women with abdominal fat had higher fasting glycemia. Systolic blood pressure was higher in overweight and obesity.